Oral Contraceptives Impair Complex Emotion Recognition in Healthy Women - Pahnke, Rike; Mau-Moeller, Anett; Junge, Martin; Wendt, Julia; Weymar, Mathias; Hamm, Alfons O.; Lischke, Alexander (Frontiers in Neuroscience, 2019)
Despite the widespread use of oral contraceptives (OCs), remarkably little is known about the effects of OCs on emotion, cognition and behavior. However, coincidental findings suggest that OCs may impair the ability to recognize the mental and emotional states of others, which may have serious consequences in interpersonal contexts. To further investigate the effects of OCs on emotion recognition, we tested whether women who were using OCs (n = 42) would be less accurate in the recognition of complex emotional states than women who were not using OCs (n = 53). In addition, we explored whether these differences in emotion recognition would depend on women’s menstrual cycle phase. We found that women with OC use were indeed less accurate in emotion recognition than women without OC use, irrespective of women’s menstrual cycle phase. Our findings indicate that OCs may, indeed, impair emotion recognition in women, which should be taken into account when informing women about the side-effects of OC use.